The Detection and Differentiation of Pigeon Adenovirus Types 1 and 2 via a High-Resolution Melting Curve Platform - Shuyu Chen; Wenyu Zhang; Zhiwang Tang; Tingting Lu; Chunhe Wan; Wensong Jin; Jiayu Li (Microorganisms, 2025)
Two main adenoviral diseases have been described in pigeons: pigeon adenovirus type 1 (PiAdV-1) and pigeon adenovirus type 2 (PiAdV-2), which belong to the genus Aviadenovirus under the family Adenoviridae. PiAdV-1 and PiAdV-2 are highly pathogenic to pigeons, leading to considerable losses worldwide. To date, there is little information on the epidemiological distribution of PiAdV-1 and PiAdV-2 in pigeons due to the lack of detection and differentiation platforms for these two viruses. High-resolution melting technology (HRM) has been widely used for developing detection and differentiation platforms, with the melting profile based on the GC content in the real-time PCR (qPCR-HRM) system. This study designed and synthesized a pair of specific primers on the basis of the characteristic variations of the 52K genes of PiAdV-1 and PiAdV-2, then the detection and differentiation qPCR-HRM platform was established after conditional optimization. The results showed that this method had good specificity; it could only specifically detect PiAdV-1 and PiAdV-2, with no cross-reaction with other pigeon-origin pathogens that occur in pigeons. This method had high sensitivity, with the lowest detection limits at 57 copies/µL (for PiAdV-1) and 56 copies/µL (for PiAdV-2). This method had good intra-group and inter-group coefficients of variation, both of which were less than 1.5%. Field samples for the epidemiological surveillance and investigation data of PiAdV-1 and PiAdV-2 were checked. We found only PiAdV-2-positive samples in meat pigeons, but the percentages of PiAdV-1-positive, PiAdV-2-positive, and coinfection-positive samples among the racing pigeons were 5.71%, 14.29%, and 2.86%, respectively. To our knowledge, this is the first report for the simultaneous detection and differentiation of PiAdV-1 and PiAdV-2 using the qPCR-HRM platform. Our study also provided evidence of PiAdV-1 and PiAdV-2 coinfection in racing pigeons, but further studies are needed.